The Kingdom of God as a Vision: a Post-critical Understanding of Luke 17:20-36 in Ricoeur’s Hermeneutics - Purwadi, Y. Slamet (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2013)
If post-critical moment is applied to the metaphor of the Kingdom of God, that is, the biblical text of the Kingdom, understanding constitutes incorporation of the world-reference and the project of hope. As a result, the central truth-content of the Kingdom of God in Luke 17:20-36, the Kingdom of God is within you, must be seen as provoking a ‘proposed world’, a world of possibilities which must be projected. The texts of the Kingdom reveal a surplus meaning: an eschatological vision, reflecting existential limitation of articulation of the Kingdom as well as a project of the Kingdom of humanity. From the perspective of mimesis theory, how the contemporary readers ‘identify’ themselves with the world of text demonstrates a followability of text. In post-critical moment, the power of the text becomes an actual ‘will’ to project the ‘impossible demand’ as the impact of textual participation with the interpretive mode of engagement-detachment. What prominent in post-critical moment is that a ‘program’ of the Kingdom is placed under the project of hope. In hermeneutic principle, the revealed truth as, part of faith truth, must be interpreted as both ontological and eschatological vision. ‘Vision’ functions as a meta-critical understanding that always destabilizes existing awareness and brings it to a futuristic horizon or eschatological openness.